Comparison of the quality of the result of digitising panoramic analogue films using transmission and reflection scanner mode with direct digital imaging standard - Azhari, Azhari; Gianto, Gianto; Suprijanto, Suprijanto (Universitas Padjadjaran, 2019)
Introduction: The use of panoramic x-ray radiographs with analogue film negatives is still widely used. Contrast differences in the radiograph are determined by the level of light transmitted from the viewer to the film negative and visual perception of the radiologist, which can cause differences and errors of interpretation. This study was aimed to compare the quality of scanners produced by the transmission and reflection modes objectively with direct digital imaging standard. Methods: This study used a descriptive comparative design with purposive sampling method. Radiographic analysis was conducted towards 30 analogue radiographs of Radiology laboratory of Universitas Padjadjaran Dental Hospital. Digitisation was performed using a scanner with setting modes (reflection and transmission, 8-bit intensity resolution and spatial resolution of 800 dpi). Digitising the negative radiographs of analogue films into digital radiographs will get a range of percentage pixels. Histogram of radiographs with a percentage of pixels in the grey level range 0 - 64 exceeds 50%, including